Polynomial representation of hybrid finite elements - Kompiš, Vladimír; Fraštia, Lubor (Computer Assisted Methods in Engineering and Science, 1997)
We introduce the hybrid-Trefftz FE formulations for linear statics of solids as well as for linear (slow velocity) steady fluid dynamics. Moving least square procedure is given to obtain continuous secondary fields (such as stresses for solids), which improves the results. For nonlinear problems the governing equations are satisfied in the discrete least square residual form. Also for such problems the hybrid FE formulation is shown.